2018
DOI: 10.1038/s41419-017-0091-7
|View full text |Cite|
|
Sign up to set email alerts
|

2,5-Hexanedione induces dopaminergic neurodegeneration through integrin αMβ2/NADPH oxidase axis-mediated microglial activation

Abstract: Recent study demonstrated that chronic exposure to solvents increases the risk of Parkinson’s disease (PD), the second most common neurodegenerative disorder characterized by progressive dopaminergic neurodegeneration in the substantia nigra (SN). n-Hexane, a widely used organic solvent, displays central-peripheral neurotoxicity, which is mainly mediated by its active metabolite, 2,5-hexanedione (HD). However, whether HD exposure contributes to PD remains unclear. In this study, we found that rats exposed to H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 61 publications
0
25
0
Order By: Relevance
“…PD is the second most common neurodegenerative disease and is characterized by a loss of dopaminergic neurons . Some environmental risk factors, such as ROT and MPP + , are used as neurotoxins for evaluating potential neuroprotective strategies against apoptotic diseases like PD .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…PD is the second most common neurodegenerative disease and is characterized by a loss of dopaminergic neurons . Some environmental risk factors, such as ROT and MPP + , are used as neurotoxins for evaluating potential neuroprotective strategies against apoptotic diseases like PD .…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that RBM3 rescues many of the deficits in the ROT‐based model of PD agrees with previous observations regarding the role of RBM3 in neuroprotection. In vitro, studies have demonstrated that RBM3 prevents apoptosis induced by excessive NO, UV irradiation, RA, staurosporine, hexanedione contact inhibition and serum deprivation, in cultured neurons or neuroblastoma cells. In vivo, it was recently found that RBM3 mediates the protective effects of hypothermia by reducing synaptic loss in a mouse model of Alzheimer's disease .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The enhanced levels of Aβ and microglial activation have been identified in patients with AD. The increasing evidence has demonstrated that NADPH oxidase partially mediates the neuroinflammation caused by Aβ plaques (Abubaker et al, 2019;Tarafdar & Pula, 2018;C. Zhang et al, 2018).…”
Section: Resveratrol and Amyloid-betamentioning
confidence: 99%
“…In detail, Pezzoli and colleagues demonstrated that n-hexane induces a specific dopamine depletion in rat Corpus striatum and behavioural defects [18,19]. More recently, Zhang and colleagues found neurodegeneration of nigrostriatal pathway in 2,5-HD-intoxicated mice with the loss of both nigral dopaminergic neurons and striatal dopaminergic terminals, thus supporting the causal effect of toxic exposure in PD etiology [20].…”
Section: Introductionmentioning
confidence: 98%